UNGKAPAN IDIOMATIS DALAM BUDAYA MASYARAKAT MINANGKABAU - Fairul Zabadi (Pusbindiklat - LIPI, 2009)
The objective of this research is to find out some idiomatic expressions in Minangkabau viewedf rom aspect form and meaning. The method used in this study is qualitative based on content analysis technique. Research findings are 27 idioms which consist of verbal idioms and nominal idioms. Verbal idioms may appear in (1) theconstruction VERB + NOUN as examplified by malapeh ao `to get no benefit' and (2) the contruction ADVERB + VERB as examplified by alah ilang 'to die'. Meanwhile, the construction of nominal idioms are three types: (1) NOUN + NOUN as examplified by kaeang miang fink, (2) NOUN + ADJECTIVE as exemplified kabau gadang'lazybones', and (3) ADJECTIVE + NOUN as examplified gadang kalang `coward'.